2009
DOI: 10.1080/03079450902737797
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a truncated pigeon circovirus capsid protein suitable for antibody detection in infected pigeons

Abstract: Infections with pigeon circovirus (PiCV) (also termed columbid circovirus) occur in meat and racing pigeons (Columba livia) of all ages and have been reported worldwide. A PiCV infection is associated with immunosuppression and the development of young pigeon disease syndrome. An indirect enzyme-linked immunosorbent assay (ELISA) for the detection of virus-specific serum antibody was developed for research purposes. In the absence of a method to propagate PiCV in cell culture, the assay was based on a recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…So far, it is known that in circovirus infection of the pigeon organism, the arising antibodies are directed against the capsid protein (Daum et al, 2009;Duchatel et al, 2011). Based on previous studies the authors of this publication agree with certain hypotheses, which argue that changes in capsid protein structure may have an influence on the formation of resistance against this virus (Cságola et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…So far, it is known that in circovirus infection of the pigeon organism, the arising antibodies are directed against the capsid protein (Daum et al, 2009;Duchatel et al, 2011). Based on previous studies the authors of this publication agree with certain hypotheses, which argue that changes in capsid protein structure may have an influence on the formation of resistance against this virus (Cságola et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A specific protocol for the prevention of PiCV infections in pigeons has not yet been developed due to the absence of vaccines targeting this pathogen. In recent years, attempts have been made to develop a recombinant PiCV capsid protein for diagnostic tests and a subunit vaccine against the PiCV (Daum et al 2009;Lai et al 2014;Stenzel et al 2016). This vaccine could protect pigeons against PiCV infection and, possibly, lower the prevalence of YPDS.…”
Section: Diagnosis Treatment and Preventionmentioning
confidence: 99%
“…Daum et al (2009) conducted a retrospective study of pigeon sera obtained in 1989, 1991 and 2008 and found anti-PiCV antibodies in 78% (61%-90%) of the tested samples on average. A recent serological study of Polish domestic pigeons from selected breeding flocks revealed the presence of anti-PiCV antibodies in 72% birds on average, regardless of their infection status (average prevalence of 36%) (Stenzel et al 2016).…”
Section: Epidemiology Of Picv Infectionsmentioning
confidence: 99%
“…The capsid protein of PiCV recognizes PiCV-specific antibodies in pigeon sera and can be used in the serodiagnosis of PiCV (Daum et al, 2009). Thus, the capsid protein mediates the induction of immune responses and has often been used to evaluate genetic changes between PiCV isolates (Stewart et al, 2006;Todd et al, 2008).…”
Section: Introductionmentioning
confidence: 99%